Dynamics and energy of starting acceleration of sprinter students and the strongest runners in the world - Kryazhev, V. D.; Petrova, R. E.; Sheveleva, A. Yu.; Karpushkin, A. A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to compare the kinetic and dynamic indicators of the starting acceleration of student sprinters and the strongest athletes in the world.